Anti-neoplastic potential of ethyl-p-methoxycinnamate of Kaempferia galanga on oral cancer cell lines - Ichwan, Solachuddin J. A.; Husin, Atiyah; Suriyah, Wastuti Hidayati; Lestari, Widya; Omar, Muhammad Nor; Kasmuri, Abdul Razak (Elsevier, 2019)
Kaempferia galanga is one of the herbal plant that have many medicinal properties. The plant extract has also been reported to possess in vitro anti-cancer activities on various cancer cell lines such as human colon cancer SW620, cervical cancer C33A, and breast cancer MCF-7 cell lines. Ethyl-p-methoxycinnamate (EPMC), a major constituent of volatile oil of Kaempferia galanga has been attributed to its medicinal benefits. We report here for the first time the anticancer potential of EPMC on oral cancer cells derived from human oral cavity, HSC-3 and Ca922 lines. MTT assay results showed that EPMC markedly induced cytotoxicity on HSC-3 (IC50 0.075 mg/mL) and Ca922 (IC50 0.085 mg/mL) cell lines. The apoptotic activity induced by EPMC was detected in both cell lines by flow cytometry and confirmed with Caspase 3/7 assay. Moreover, quantitative RT-PCR analysis revealed that EPMC-induced apoptosis in both lines elevated the mRNA levels of pro-apoptotic genes caspase-9 and PUMA. These results suggest that EPMC may be a potential candidate for oral cancer treatment.